KERAPATAN DAN LUAS PERMUKAAN MANGROVE DI PESISIR KARANG INDAH DAN LAMPU SATU DISTRIK MERAUKE KABUPATEN MERAUKE - Siti Masiyah (AGRICOLA, 2014)
Merauke district, which located inSouthern Papua has extensive mangrove ecosystem. In 2009, Meraukehas  4672.382 hectares ecosystem mangrove. The aims this research was determined the density and extensive of ecosystem mangrove according to standard on PP No. 201/2004 about standard quality and criteria mangrove destruction. This research conducted on September until December 2014. The methodology using transects system in sampling area. The sampling area was on coastal Karang Indah and Lampu Satu. The results show that the density of mangroves in Karang Indah, between 1200-20 tress /ha with area closures between 91.4 to 0.1%. According the standard, the density of mangrove was good. Meanwhile, the density of mangroves in Lampu Satu, among 603-11 trees/ ha with area closures between 49.2 - 0.1%. According to the standard, this area was raredensity and damaged.